Effect of measles vaccination in infants younger than 9 months on the immune response to subsequent measles vaccine doses: a systematic review and meta-analysis. Issue 11 (November 2019) - Nic Lochlainn, Laura M; de Gier, Brechje; van der Maas, Nicoline; van Binnendijk, Rob; Strebel, Peter M; Goodman, Tracey; de Melker, Hester E; Moss, William J; Hahné, Susan J M
Summary: Background: Vaccinating infants with a first dose of measles-containing vaccine (MCV1) before 9 months of age in high-risk settings has the potential to reduce measles-related morbidity and mortality. However, there is concern that early vaccination might blunt the immune response to subsequent measles vaccine doses. We systematically reviewed the available evidence on the effect of MCV1 administration to infants younger than 9 months on their immune responses to subsequent MCV doses. Methods: For this systematic review and meta-analysis, we searched for randomised and quasi-randomised controlled trials, outbreak investigations, and cohort and case-control studies without restriction on publication dates, in which MCV1 was administered to infants younger than 9 months. We did the literature search on June 2, 2015, and updated it on Jan 14, 2019. We included studies reporting data on strength or duration of humoral and cellular immune responses, and on vaccine efficacy or vaccine effectiveness after two-dose or three-dose MCV schedules. Our outcome measures were proportion of seropositive infants, geometric mean titre, vaccine efficacy, vaccine effectiveness, antibody avidity index, and T-cell stimulation index. We used random-effects meta-analysis to derive pooled estimates of the outcomes, where appropriate. We assessed the methodological quality of included studies using Grading of Recommendation Assessment, Development and Evaluation (GRADE) guidelines. Findings: Our search retrieved 1156 records and 85 were excluded due to duplication. 1071 records were screened for eligibility, of which 351 were eligible for full-text screening and 21 were eligible for inclusion in the review. From 13 studies, the pooled proportion of infants seropositive after two MCV doses, with MCV1 administered before 9 months of age, was 98% (95% CI 96–99; I 2 =79·8%, p<0·0001), which was not significantly different from seropositivity after a two-dose MCV schedule starting later (p=0·087). Only one of four studies found geometric mean titres after MCV2 administration to be significantly lower when MCV1 was administered before 9 months of age than at 9 months of age or later. There was insufficient evidence to determine an effect of age at MCV1 administration on antibody avidity. The pooled vaccine effectiveness estimate derived from two studies of a two-dose MCV schedule with MCV1 vaccination before 9 months of age was 95% (95% CI 89–100; I 2 =12·6%, p=0·29). Seven studies reporting on measles virus-specific cellular immune responses found that T-cell responses and T-cell memory were sustained, irrespective of the age of MCV1 administration. Overall, the quality of evidence was moderate to very low. Interpretation: Our findings suggest that administering MCV1 to infants younger than 9 months followed by additional MCV doses results in high seropositivity, vaccine effectiveness, and T-cell responses, which are independent of the age at MCV1, supporting the vaccination of very young infants in high-risk settings. However, we also found some evidence that MCV1 administered to infants younger than 9 months resulted in lower antibody titres after one or two subsequent doses of MCV than when measles vaccination is started at age 9 months or older. The clinical and public-health relevance of this immunity blunting effect are uncertain. Funding: WHO.